STRATEGI MASJID DALAM PEMBERDAYAAN EKONOMI UMAT - Sukarno L. Hasyim (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2016)
Islam is a perfect religion which the teachings include and take care the problems of human life. The teachings of Islam regulate the human behavior, both regard as God's creatures as well as fellow beings, in terms of Usul Fiqh or Fiqh called the Sharia. the issues related to economic problems has been set in Islam. Islam applied the economic system by using of moral and law together for uphold the building a system that practical. Economic according to Islam is a set of common economic fundamentals are inferred from the Qur'an and Sunnah, and a building which built on the foundations of according to each environment and period. Islamic rules about the economy including the rules of perfect and complete. Therefore, the application of the Islamic economic system in economic structure of community most likely will bring more to welfare and benefit of society itself. One of them is the economic empowerment of sharia through the mosques. The mosque is the smallest base closest to the Muslim community. Apart as the center of worship, Mosque can also serve as a medium of religious social development in economy to raise the welfare of people. For example, around the mosque can be used as sharia cooperative development center that recently received positive reception among the public. The goal is nothing else to fulfill the spiritual and material welfare of the pilgrims in order to create welfare in this world and hereafter.